Sustainability in prickly pear production in San Pablo Xúchil, Axapusco - Rodríguez-Ramírez, Tania; Jiménez-Velázquez, Mercedes Aurelia; Fuentes-Castillo, María Janet; Tello-García, Enriqueta (Revista Mexicana de Ciencias Agrícolas, 2025)
The research aims to analyze the traditional and conventional production systems of prickly pear (Opuntia albicarpa) to identify their current sustainability, as well as the social, environmental, and economic relevance that this crop represents for the community. In the eastern region of the state of Mexico, several municipalities stand out for their deep-rooted tradition in the production of prickly pear. In the locality of San Pablo Xúchil, this activity has taken on a central relevance, not only economically, but also culturally. Nonetheless, production has been questioned in terms of its sustainability due to the adoption of practices that are harmful to the environment: monoculture and intensive use of agrochemicals. A questionnaire was applied to 44 prickly pear producers with the framework for the evaluation of natural resource management systems, incorporating sustainability indicators. Fifteen indicators were analyzed with the following dimensions: environmental, economic, and social. The results obtained show that both systems need to increase their sustainability, as a result of weak organization, low training, and high use of agrochemicals.
Keywords: Community; MESMIS; Opuntia albicarpa; sustainable development